Critical Thinking and Academic Achievement among Secondary and Senior Secondary School Students - Sherafat, Roya Sherafat; Murthy, C.G. Venkatesha (INDIAN EDUCATIONAL REVIEW, 2016)
The study examined the effect of critical thinking on academic achievement among secondary and senior secondary school students of Mysuru. It also attempted to find out the variations in the critical thinking abilities of secondary and senior secondary level students. The study was conducted on a sample of 625 students of Mysuru City in India using stratified random sampling technique. Murthy’s (2014) Mysuru Critical Thinking Scale was administered. Results indicated that the students’ academic achievement was affected by their critical thinking. The students with higher levels of critical thinking did better on academic achievement as compared to their low counterparts. Further, there was no difference between the secondary and senior secondary students on their critical thinking abilities. Results shows that critical thinking is an important factor and a correlate of academic achievement.